Thermal Decomposition Studies of Lanthanide(III) Complexes of Diethylenetriaminepentaacetic Acid - S. Kumar, Asha; Indrasenan, P. (Asian Journal of Chemistry, 2010)
Thermal decomposition studies of lanthanide(III) complexes of diethylenetriaminepentaacetic acid (DTPA) in air is studied using simultaneous TG-DTA. Nine lanthanides chosen are La, Pr, Nd, Sm, Eu, Gd, Tb, Dy and Yb. The phenomenological as well as the kinetic aspects of thermal decomposition is described. Kinetic parameters are calculated. The stability of the complexes in air is assessed.